Silicon carbide piezoelectric catalytic film and preparation method and application thereof

CN122974160APending Publication Date: 2026-10-27NINGXIA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611468316.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本申请旨在解决现有技术中压电催化膜在PE-PMS体系中,粉末催化剂难以回收、膜基底材料在高温强碱水热条件下稳定性差,以及因缺乏有效的界面过渡层导致压电催化相与膜基底之间结合力弱、催化组分在超声振动和流体冲刷下易脱落,且现有膜基底材料难以同时满足PE-PMS体系耐强酸强碱腐蚀和耐高温水热合成要求的技术问题

Benefits of technology

1.本申请通过设置由锐钛矿型TiO2和硅氧组分组成的复合诱导层,构建了“纯质SiC基底-复合诱导层-BaTiO3催化相”的多级结构。其中,复合诱导层中的锐钛矿型TiO2为BaTiO3的原位生长提供钛源和成核位点,复合诱导层中的硅氧组分作为界面过渡组分和无机粘结组分,改善锐钛矿型TiO2在碳化硅晶粒表面的铺展与附着稳定性,降低复合诱导层在强碱水热和超声使用过程中的剥离脱落风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974160A_ABST
    Figure CN122974160A_ABST
Patent Text Reader

Abstract

The application provides a silicon carbide piezoelectric catalytic film and a preparation method and application thereof. The catalytic film comprises a pure silicon carbide film substrate, a composite induction layer formed on the surface of the film substrate, and BaTiO3 particles loaded on the composite induction layer; the composite induction layer comprises a TiO2 component and a silicon-oxygen component. In the preparation, the pure silicon carbide film is immersed in a Ti-Si composite precursor sol, dried and calcined to form a composite induction layer, and then placed in a barium-containing alkaline reaction solution for hydrothermal treatment, so that the TiO2 component induces the formation of BaTiO3 particles. The obtained composite catalytic film can be used for mechanical vibration assisted persulfate activation and organic pollutant treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of environmental catalytic materials and membrane separation materials, specifically to a silicon carbide piezoelectric catalytic membrane, its preparation method, and its application. Background Technology

[0002] Piezoelectric catalysis technology can generate polarized charges using mechanical energy such as ultrasound, mechanical vibration, or fluid disturbance, and has potential advantages such as catalyst reusability and reduced need for powder separation and recovery, making it a research hotspot in the field of water treatment. Persulfate (PMS)-based advanced oxidation technology has attracted much attention due to its strong oxidizing power and wide pH applicability. Combining piezoelectric catalysis technology with PMS (hereinafter referred to as the "PE-PMS system") utilizes the polarized charges generated by the piezoelectric material under external force to activate PMS, producing ·OH... 1 O2, SO4· - The synergistic degradation of pollutants by various highly reactive oxygen species (ROS) is a cutting-edge direction in the field of water treatment. Barium titanate, due to its lead-free composition, high piezoelectric constant, and good chemical stability, is the preferred piezoelectric catalytic material in the PE-PMS system.

[0003] However, the following challenges remain in advancing the PE-PMS catalytic system from laboratory concept to practical engineering applications: Firstly, powdered barium titanate piezoelectric catalysts are prone to agglomeration, separation, and loss in water, making subsequent recovery difficult and hindering the integration of separation and catalysis in continuous flow membrane separation processes. Immobilizing the catalyst on a membrane substrate is a feasible solution to the recovery problem, but existing methods for preparing piezoelectric catalytic membranes generally suffer from weak interfacial bonding between the catalyst layer and the membrane substrate. For example, patent document CN119926195A, entitled "A Piezoelectric Photocatalytic Self-Cleaning Hollow Fiber Ceramic Membrane and Its Preparation Method and Application," discloses a technical solution for forming a barium titanate-based material on the surface of a ceramic membrane, but it does not focus on disclosing the Ti-Si interfacial transition layer used in strong alkaline hydrothermal processes, nor does it systematically explain the interfacial stability of the formed catalyst layer under long-term ultrasonic vibration conditions.

[0004] Secondly, the substrate materials of existing piezoelectric catalytic membranes are difficult to adapt to the actual operating conditions of the PE-PMS system. Organic polymer membranes may have limitations in thermal stability and oxidation resistance under high-temperature hydrothermal and long-term strong oxidation conditions; some alumina-based membranes may experience surface corrosion or structural damage under high-temperature and strong alkaline conditions. Existing related technologies do not focus on disclosing the Ti-Si composite interface transition layer and its interface stability under long-term ultrasonic conditions. Even when using silicon carbide membranes as substrates, existing SiC membrane catalytic preparation processes still have limitations. For example, patent CN114515587A discloses a method for growing TiO2 nanostructures on silicon carbide films by sol-coating combined with hydrothermal method, and then loading V2O5-WO3 denitration catalyst on the TiO2 nanostructures. This patent provides a technical inspiration for piezoelectric catalytic membrane substrate materials for PE-PMS systems. However, its TiO2 layer is a single-component structure, and the interfacial bonding force between the single TiO2 layer and the SiC substrate is limited. In the subsequent high-temperature strong alkaline hydrothermal reaction to generate barium titanate and the ultrasonic catalytic reaction, there is a risk of detachment from the substrate silicon carbide layer.

[0005] To simultaneously achieve the dual functions of a PE-PMS catalytic system and membrane separation technology, the membrane material must maintain long-term structural stability during catalytic use. A robust bonding layer needs to be formed between the catalytic layer and the membrane substrate to prevent the catalytic components from detaching due to ultrasonic vibration and fluid erosion. Simultaneously, the membrane substrate material itself needs to possess resistance to strong acid and alkali corrosion and high-flux separation characteristics to adapt to wastewater treatment scenarios with a wide pH range. Current technologies do not provide a piezoelectric catalytic membrane preparation scheme that simultaneously meets the above requirements for both substrate material and interfacial bonding. Summary of the Invention

[0006] This application aims to solve the technical problems in the prior art of piezoelectric catalytic membranes in PE-PMS systems, such as the difficulty in recovering powdered catalysts, poor stability of membrane substrate materials under high temperature and strong alkaline hydrothermal conditions, weak bonding between the piezoelectric catalytic phase and the membrane substrate due to the lack of an effective interfacial transition layer, easy detachment of catalytic components under ultrasonic vibration and fluid scouring, and the inability of existing membrane substrate materials to simultaneously meet the requirements of strong acid and strong alkali corrosion resistance and high temperature hydrothermal synthesis resistance of PE-PMS systems.

[0007] To solve the above-mentioned technical problems, this application provides the following technical solution: In a first aspect, this application provides a silicon carbide piezoelectric catalytic membrane, comprising a pure silicon carbide membrane substrate, a composite induction layer supported on the pure silicon carbide membrane substrate, and BaTiO3 particles supported on the composite induction layer; the composite induction layer comprises a TiO2 component and a silicon-oxygen component; BaTiO3 is barium titanate particles generated in situ on the surface of TiO2.

[0008] Preferably, the TiO2 composition is anatase TiO2.

[0009] Preferably, the pure silicon carbide membrane is one of a single-channel tubular membrane, a multi-channel tubular membrane, or a sheet membrane.

[0010] Secondly, this application also provides a method for preparing a silicon carbide piezoelectric catalytic membrane, wherein a pure silicon carbide membrane substrate is immersed in a Ti-Si composite sol for impregnation and coating, dried, and then calcined in an air atmosphere at 450-550°C. After calcination, the substrate is then immersed in a strongly alkaline reaction solution containing a barium source for hydrothermal reaction.

[0011] Preferably, the preparation method of Ti-Si composite sol is as follows: Tetrabutyl titanate and anhydrous ethanol are mixed, and acetylacetone is added to obtain solution A; deionized water, dispersant and anhydrous ethanol are mixed, tetraethyl orthosilicate is added, and the pH is adjusted to 2.0-2.5 with acid to obtain solution B; solution B is added dropwise to solution A, stirred and aged to obtain Ti-Si composite sol.

[0012] Preferably, the dispersing agent is polyvinylpyrrolidone; the mass of polyvinylpyrrolidone is 3% to 10% of the mass of tetrabutyl titanate; and the molar ratio of deionized water to tetrabutyl titanate is (1.0 to 3.5):1.

[0013] Preferably, the mass of the silicon source in solution B, calculated as SiO2, accounts for 1% to 5% of the sum of the mass of the titanium source in solution A, calculated as TiO2, and the mass of the silicon source in solution B, calculated as SiO2.

[0014] Preferably, the impregnation coating is performed by multiple impregnation and lifting, with 1 to 5 impregnations, each impregnation time being 10 to 60 seconds, the lifting rate being 2 to 8 mm / s, and drying at 80 to 120°C for 5 to 15 minutes after each impregnation.

[0015] Preferably, the strongly alkaline reaction solution uses KOH or NaOH to provide an alkaline environment and Ba(OH)2 to provide a barium source.

[0016] Preferably, the concentration of KOH or NaOH is 0.5–1.0 M.

[0017] Preferably, the concentration of Ba(OH)2 is 0.03–0.1 M.

[0018] Preferably, after the hydrothermal reaction is completed, the prepared silicon carbide piezoelectric catalytic membrane is taken out, rinsed with deionized water until neutral, and then dried.

[0019] Preferably, the heating rate of calcination is 1-3℃ / min, and the holding time is 60-180min.

[0020] Preferably, the hydrothermal reaction temperature is 180–220°C, and the holding time is 18–48 h.

[0021] Thirdly, this application also provides the application of the aforementioned silicon carbide piezoelectric catalytic membrane in the treatment of organic wastewater.

[0022] The technical advantages of this application are as follows: 1. This application constructs a multi-level structure of "pure SiC substrate - composite induction layer - BaTiO3 catalytic phase" by setting a composite induction layer composed of anatase TiO2 and silicon-oxygen components. The anatase TiO2 in the composite induction layer provides a titanium source and nucleation sites for the in-situ growth of BaTiO3, while the silicon-oxygen components in the composite induction layer serve as interfacial transition components and inorganic binders, improving the spreading and adhesion stability of anatase TiO2 on the silicon carbide grain surface and reducing the risk of peeling off the composite induction layer during strong alkaline hydrothermal and ultrasonic use.

[0023] 2. This application uses pure silicon carbide film as substrate, which has the characteristics of strong acid and alkali resistance, high porosity, high flux and high mechanical strength. It can be adapted to the high temperature and strong alkaline environment of barium titanate hydrothermal growth, and is also compatible with the strong oxidizing conditions of PMS system. Under the hydrothermal conditions of the embodiment, the recrystallized SiC substrate shows good structure retention ability, which is beneficial to improving the stability of the catalytic film under strong alkaline hydrothermal and ultrasonic conditions.

[0024] 3. This application achieves the construction of a composite induced layer and the in-situ growth of BaTiO3 by combining Ti-Si composite sol impregnation coating with a high-temperature strong alkali hydrothermal method; BaTiO3 has excellent piezoelectric properties and is grown in situ on both the membrane surface and the inner wall of the membrane pores, forming three-dimensional catalytic active sites, ensuring sufficient catalytic active sites and piezoelectric response performance; the preparation process is simple and controllable.

[0025] 4. The silicon carbide piezoelectric catalytic membrane prepared in this application possesses both membrane separation and piezoelectric catalytic functions, enabling synergistic effects of physical retention and chemical degradation of pollutants in organic wastewater treatment. Under ultrasonic vibration conditions, it can efficiently activate PMS and significantly enhance the activity of reactive oxygen species (·OH, ·OH, ·OH). 1 O2, SO4· - The generation efficiency and degradation performance of organic pollutants (etc.) are improved; the ultrasonic-driven PMS activation method does not require an additional power source and has lower energy consumption than the electrochemical activation system. Attached Figure Description

[0026] Figure 1 SEM comparison images of pure silicon carbide film and hydrothermally treated silicon carbide film in this application (ab: surface of pure silicon carbide film, cf: surface of film after hydrothermal treatment, gh: cross-section of film after hydrothermal treatment). Figure 2 The X-ray diffraction patterns of the pure silicon carbide film and the silicon carbide film grown in situ after barium titanate in Example 1 of this application are shown. Figure 3 Comparative Example 2: Comparative images of barium titanate before and after hydrothermal growth of γ-Al2O3 sheet ceramic membrane (ab) and non-pure silicon carbide ceramic membrane (cd, sheet type; ef, tubular type). Figure 4 The graph shows the performance of pure silicon carbide membrane and silicon carbide piezoelectric catalytic membrane prepared in Examples 1, 2 and 3 of this application in degrading Rhodamine B. Figure 5 The graph shows the recycling performance of the silicon carbide piezoelectric catalytic membrane prepared in Example 1 of this application for the degradation of Rhodamine B. Detailed Implementation

[0027] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application, and are therefore merely examples and should not be used to limit the scope of protection of this application.

[0028] This application first provides a silicon carbide piezoelectric catalytic membrane, comprising a pure silicon carbide membrane substrate, a composite induction layer supported on the pure silicon carbide membrane substrate, and BaTiO3 particles supported on the surface of the composite induction layer.

[0029] The pure silicon carbide film substrate was prepared using a high-temperature recrystallization process, and the silicon carbide grains formed a porous network structure through neck connections. (See also...) Figure 1 (ab) The pure silicon carbide membrane has smooth and rounded silicon carbide grain surfaces, with obvious neck-connecting phases between grains, and a uniformly distributed pore network on the membrane surface. The pure silicon carbide membrane possesses characteristics such as resistance to strong acids and alkalis, high temperature resistance, high porosity, high flux, and high mechanical strength. It provides a porous support structure for membrane separation and a corrosion-resistant and mechanically stable substrate for subsequent strongly alkaline hydrothermal reactions.

[0030] The composite inducing layer is composed of anatase TiO2 and silicon-oxygen components; the BaTiO3 is composed of barium titanate particles generated in situ on the TiO2 surface. See also Figure 2 The X-ray diffraction pattern shows that TiO2 after sol impregnation and calcination exhibits diffraction peaks characteristic of the anatase phase.

[0031] See Figure 1 (cf) BaTiO3 is uniformly distributed on the silicon carbide film, and barium titanate particles grow in situ along the surface of the TiO2 induced layer, forming strips that stack together to create a "coral" morphology. See also Figure 1 (cf) shows that barium titanate is also uniformly distributed across the cross-section of the silicon carbide film, and in-situ growth of a titanium dioxide-induced layer and barium titanate particles is observed within the film pores. Figure 1 It can be seen that barium titanate has achieved full growth on the membrane surface and within the pores.

[0032] In one embodiment of this application, the pure silicon carbide film is one of a single-channel tubular film, a multi-channel tubular film, or a sheet film.

[0033] This application also provides a method for preparing the above-mentioned silicon carbide piezoelectric catalytic membrane, wherein a pure silicon carbide membrane substrate is immersed in Ti-Si composite sol for impregnation and coating, dried, and then calcined in an air atmosphere at 450-550°C, and then immersed in a strong alkaline reaction solution containing barium source for hydrothermal reaction.

[0034] The preparation method includes the following steps: Step 1: Pretreatment of pure silicon carbide film substrate The pure silicon carbide film was ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water, and then dried for later use.

[0035] Step 2: Preparation of Ti-Si composite sol Tetrabutyl titanate (TBOT) was mixed with anhydrous ethanol, and acetylacetone was added to obtain solution A; deionized water, dispersant, and anhydrous ethanol were mixed, and tetraethyl orthosilicate was added, and the pH was adjusted to 2.0-2.5 with acid to obtain solution B; solution B was added dropwise to solution A, stirred, and aged to obtain the Ti-Si composite sol, wherein the acid was one of hydrochloric acid and nitric acid.

[0036] The dispersing agent is preferably polyvinylpyrrolidone (PVP). PVP acts as a sol stabilizer and film-forming aid to improve the stability of the precursor sol and the continuity of the impregnation layer. Maintaining the pH at 2.0–2.5 can slow down the rapid hydrolysis of the titanium source and maintain the stability of the sol during impregnation coating.

[0037] In one embodiment of this application, the mass of the polyvinylpyrrolidone is 3% to 10% of the mass of the tetrabutyl titanate; the molar ratio of the deionized water to the tetrabutyl titanate is (1.0 to 3.5):1.

[0038] When the PVP content is too low, it may be difficult to adequately improve the stability of the sol; when the content is too high, it may increase the amount of organic matter removed during the calcination process and increase the risk of pores or cracks in the coating.

[0039] The amount of water is used to adjust the degree of hydrolysis and condensation of the titanium source and silicon source, and the specific ratio can be selected according to the stability of the sol and the coating performance.

[0040] In one embodiment of this application, the mass of the silicon source, calculated as SiO2, accounts for 1% to 5% of the sum of the mass of the titanium source, calculated as TiO2, and the mass of the silicon source, calculated as SiO2.

[0041] Step 3: Sol-gel impregnation coating The pretreated silicon carbide film is vertically immersed in the above-mentioned Ti-Si composite sol for immersion coating. The immersion coating is performed 1-5 times, with a single immersion time of 10-60s and a pulling rate of 2-8mm / s. After each immersion, the film is dried at 80-120℃ for 5-15min to obtain a silicon carbide film coated with gel.

[0042] During the impregnation and coating stage, the Ti-Si composite sol penetrates into the pores of the SiC membrane through capillary action. After calcination, a composite induced layer is formed on both the membrane surface and the inner wall of the pores. In the subsequent strongly alkaline hydrothermal reaction, the reaction solution containing KOH or NaOH and Ba(OH)2 penetrates into the membrane through the pores, alkali etching the TiO2 induced layer on the inner wall of the pores and growing BaTiO3 in situ.

[0043] Step 4: Calcination The coated silicon carbide film was placed in a muffle furnace for calcination at a temperature of 450-550℃, a heating rate of 1-3℃ / min, and a holding time of 60-180min. The film was then allowed to cool naturally to room temperature to obtain a silicon carbide film loaded with a composite induced layer containing TiO2 and silicon-oxygen components.

[0044] The heating rate during calcination should be controlled at 1–3 °C / min. If the heating rate is below 1 °C / min, the calcination cycle is too long, resulting in low production efficiency; if the heating rate is above 3 °C / min, the organic matter in the gel decomposes too quickly, and the resulting gas is released rapidly, causing the coating to blister or crack. The holding time should be 60–180 min.

[0045] Calcination at 450–550 °C is beneficial for removing organic components and promoting TiO2 crystallization; too low a temperature may result in organic residues, while too high a temperature or too long a holding time may result in grain growth and change the TiO2 phase composition.

[0046] Step 5: Hydrothermal in-situ growth of barium titanate Dissolve 0.5-1.0 M KOH in deionized water by stirring, then add 0.03-0.1 M Ba(OH)₂·8H₂O by stirring to obtain a barium source reaction solution. Immerse a silicon carbide membrane loaded with a composite induced layer containing TiO₂ and silicon-oxygen components in the barium source reaction solution for a hydrothermal reaction at 180-220℃ for 18-48 h. After cooling, remove the membrane, rinse with deionized water until neutral, and dry to obtain a silicon carbide piezoelectric catalytic membrane with barium titanate particles coating silicon carbide grains.

[0047] Hydrothermal temperature and time affect the amount of BaTiO3 particles formed, the degree of crystallinity, and the particle size. Too low a temperature or time may lead to incomplete reaction; too high a temperature or too long a time may increase the risk of particle coarsening, non-uniform deposition, and damage to the composite induced layer.

[0048] In one embodiment of this application, the strongly alkaline reaction solution provides an alkaline environment with KOH or NaOH and a barium source with Ba(OH)2; the concentration of KOH or NaOH is 0.5-1.0M and the concentration of Ba(OH)2 is 0.03-0.1M.

[0049] KOH or NaOH provides a strongly alkaline environment in the reaction solution. Its functions include: promoting hydroxylation and partial dissolution of the TiO2 surface, forming surface-activated titanium species or titanate species that can participate in the formation of the BaTiO3 phase, providing a titanium source for the lattice construction of BaTiO3; and providing the alkaline medium conditions required for the hydrothermal synthesis of BaTiO3. The concentration range described herein balances TiO2 surface activation and the maintenance of the composite induced layer structure under the conditions of this embodiment. Excessive alkali concentration or barium source concentration may increase the risk of side reactions in the solution phase or non-uniform deposition. The following specific examples and comparative examples further illustrate the implementation of this application.

[0050] Example 1 The preparation of a silicon carbide piezoelectric catalytic membrane includes the following steps: Step 1: Take the pure, single-channel tubular silicon carbide membrane (with an inner diameter of 8 mm, an outer diameter of 12 mm, a length of 60 mm, a pore size of about 1.6 µm, and a porosity of about 40%) prepared by recrystallization process, and place it in acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning for 10 min each, and dry it in an oven at 60 °C for 1 h for later use.

[0051] Step 2: Mix 8.5g of tetrabutyl titanate (TBOT) with 38mL of anhydrous ethanol, add 2.55mL of acetylacetone (molar ratio of TBOT to 1:1) while stirring, and stir for 15min to obtain solution A; mix 1.58mL of deionized water (H2O / TBOT=3.5:1) with 5mL of anhydrous ethanol, add 0.85g of polyvinylpyrrolidone (PVP-K30, 10% of the mass of TBOT) and stir until completely dissolved, add 0.15mL of tetraethyl orthosilicate (the amount of tetraethyl orthosilicate added is based on the mass of SiO2, accounting for 2% of the total mass of TiO2 and SiO2), sonicate for 10min, and adjust the pH to 2.0 with concentrated nitric acid (68%) to obtain solution B; add solution B dropwise to solution A at a rate of 1 drop / 1.5s, stir at 600rpm for 40min, seal and age at room temperature for 18h to obtain Ti-Si composite sol.

[0052] Step 3: Vertically immerse the pretreated silicon carbide film into the above Ti-Si composite sol, immerse 3 times, 30s each time, with a pulling speed of 5mm / s, and dry at 100℃ for 10min after each immersion.

[0053] Step 4: Place the coated silicon carbide film into a muffle furnace, heat it to 450℃ at a rate of 2℃ / min, hold it at that temperature for 120 minutes, and then let it cool naturally to room temperature with the furnace.

[0054] Step 5: Add 4.49g KOH to 80mL of deionized water and stir to dissolve. Then add 2.02g Ba(OH)2·8H2O and stir to obtain a barium source reaction solution. Place the silicon carbide membrane loaded with a composite induction layer containing anatase TiO2 and silicon-oxygen components into a 100mL polytetrafluoroethylene-lined hydrothermal reactor. Pour in the reaction solution to completely immerse the membrane. After sealing, perform a hydrothermal reaction at 195℃ for 40h. After cooling, remove the membrane, rinse with deionized water until neutral, and dry at 60℃ for 1h to obtain a silicon carbide piezoelectric catalytic membrane.

[0055] Example 2 The only difference between this embodiment and Embodiment 1 is that in step 1, a multi-channel tubular membrane (with a diameter of 40 mm, a length of 80 mm, a total of 37 channels, each channel having a diameter of 4 mm, a membrane tube pore size of approximately 5.0 µm, and a porosity of approximately 50%) is used.

[0056] In step 2, 17g of tetrabutyl titanate (TBOT) was mixed with 76mL of anhydrous ethanol, and 5.1mL of acetylacetone (molar ratio of TBOT to 1:1) was added while stirring. The mixture was stirred for 15min to obtain solution A. 0.9mL of deionized water (H2O / TBOT=1:1) was mixed with 10mL of anhydrous ethanol, and 0.51g of polyvinylpyrrolidone (PVP, 3% of the mass of TBOT) was added and stirred until completely dissolved. 0.15mL of tetraethyl orthosilicate was added (the amount of tetraethyl orthosilicate added was calculated based on the mass of SiO2, accounting for approximately 1% of the total mass of TiO2 and SiO2).

[0057] In step 4, the coated silicon carbide film is placed in a muffle furnace, heated to 550°C at a rate of 2°C / min, held at that temperature for 120 min, and then allowed to cool naturally to room temperature with the furnace.

[0058] In step 5, 4.49 g KOH was added to 160 mL of deionized water and stirred to dissolve. Then, 2.02 g Ba(OH)2·8H2O was added and stirred to obtain a barium source reaction solution. The silicon carbide membrane loaded with a composite induction layer containing anatase TiO2 and silicon-oxygen components was placed in a 200 mL polytetrafluoroethylene-lined hydrothermal reactor. The reaction solution was poured in to completely immerse the membrane. After sealing, the membrane was hydrothermally reacted at 180 °C for 48 h. After cooling, the membrane was removed, rinsed with deionized water until neutral, and dried at 60 °C for 1 h to obtain a silicon carbide piezoelectric catalytic membrane.

[0059] The remaining steps and parameters are the same as in Example 1.

[0060] Example 3 The only difference between this embodiment and Embodiment 1 is that in step 1, a sheet-like membrane (with a diameter of 21 mm, a thickness of 2.1 mm, a pore size of about 0.4 µm, and a porosity of about 37%) is used.

[0061] In step 2, 0.9 mL of deionized water (H2O / TBOT=2:1) ​​and 5 mL of anhydrous ethanol were mixed, and 0.425 g of polyvinylpyrrolidone (PVP-K30, 5% of the mass of TBOT) was added and stirred until completely dissolved. Then, 0.39 mL of tetraethyl orthosilicate was added (the amount of tetraethyl orthosilicate added was based on the mass of SiO2, accounting for about 5% of the total mass of TiO2 and SiO2).

[0062] In step 4, the coated silicon carbide film is placed in a muffle furnace, heated to 500°C at a rate of 2°C / min, held at that temperature for 120 min, and then allowed to cool naturally to room temperature with the furnace.

[0063] In step 5, 4.49 g KOH was added to 80 mL of deionized water and stirred to dissolve. Then, 2.52 g Ba(OH)2·8H2O was added and stirred to obtain a barium source reaction solution. After sealing, the solution was subjected to hydrothermal reaction at 220 °C for 18 h.

[0064] The remaining steps and parameters are the same as in Example 1.

[0065] Comparative Example 1 The only difference between this embodiment and Embodiment 1 is that in step 2, tetraethyl orthosilicate is not added when preparing the sol, resulting in a silicon-oxygen-free component with only a TiO2-induced layer.

[0066] The remaining steps and parameters are the same as in Example 1.

[0067] Comparative Example 2 The only difference between this embodiment and Embodiment 1 is that, in step 1, a γ-Al2O3 sheet ceramic membrane (with a pore size of about 0.4µm) is used instead of a pure silicon carbide membrane.

[0068] The remaining steps and parameters are the same as in Example 1.

[0069] Comparative Example 3 The only difference between this embodiment and Embodiment 1 is that, in step 1, a non-pure silicon carbide wafer-type ceramic film is used instead of a pure silicon carbide film.

[0070] The remaining steps and parameters are the same as in Example 1.

[0071] See Figure 3 a and b are comparative images of the alumina film in Comparative Example 2 before and after hydrothermal growth; cf are comparative images of the impure silicon carbide film (reaction sintered film) in Comparative Example 3 before and after hydrothermal growth. See also Figure 3Under the hydrothermal conditions used in the examples, the tested γ-Al₂O₃ film and reaction-sintered SiC film showed significant corrosion or structural damage. This demonstrates that pure silicon carbide films are irreplaceable for the high-temperature, strong-alkali hydrothermal growth of barium titanate.

[0072] This application also provides the application of the aforementioned silicon carbide piezoelectric catalytic membrane in the treatment of organic wastewater.

[0073] In one embodiment of this application, the organic wastewater treatment is as follows: under ultrasonic vibration conditions, the silicon carbide piezoelectric catalytic membrane activates persulfate to generate active oxygen species, thereby degrading organic pollutants in the wastewater.

[0074] The organic wastewater includes, but is not limited to, wastewater containing organic pollutants such as Rhodamine B, tetracycline, and methylene blue. The silicon carbide piezoelectric catalytic membrane combines membrane separation and piezoelectric catalytic degradation functions in organic wastewater treatment: the membrane separation function physically retains suspended particulate matter and colloidal pollutants in the wastewater; the piezoelectric catalytic function activates persulfate to generate reactive oxygen species, thereby achieving the chemical degradation of dissolved organic pollutants.

[0075] Application Example 1: Under the conditions of 40kHz, 120W ultrasound as the external vibration source, temperature 25℃, cross-flow operation mode, and transmembrane pressure of 0.1 bar, the piezoelectric catalytic membranes prepared in Examples 1, 2, and 3 were used to mix 50 mL of 0.1 g / L RhB solution with 50 mL of 0.4 g / L PMS solution, for a total volume of 100 mL. The initial concentrations of RhB and PMS after mixing were 0.05 g / L and 0.20 g / L, respectively. Before the reaction, the membrane was placed in RhB solution in the dark to adsorb to equilibrium, and the concentration after adsorption equilibrium was defined as C0. Subsequently, PMS was added and ultrasound was turned on. The results are shown in Table 1.

[0076] Table 1. Degradation rate of Rhodamine B within 60 min See Table 1 and Figure 4 The US / PMS system alone, the PMS system alone, and the US / PMS system without a membrane all showed some apparent removal of RhB, indicating that both ultrasonic treatment and direct oxidation by PMS may contribute to RhB removal. The apparent removal rate of the pure SiC membrane / US / PMS system was slightly higher than that of the US / PMS system without a membrane, indicating that the additional contribution introduced by the pure SiC membrane was relatively limited.

[0077] Example 1: A single-tube silicon carbide piezoelectric catalytic membrane coupled with PMS showed significant degradation of Rhodamine B under ultrasonication, with a degradation rate of 97.5% within 60 minutes. Example 2: A multi-channel silicon carbide piezoelectric catalytic membrane coupled with PMS achieved a 100.0% degradation rate of Rhodamine B under ultrasonication within 60 minutes. Example 3: A disc-type silicon carbide piezoelectric catalytic membrane coupled with PMS achieved a 92.7% degradation rate of Rhodamine B within 60 minutes. All three types of pure silicon carbide membranes achieved degradation rates exceeding 92%, indicating that this process can be applied to SiC membranes with different geometries.

[0078] The difference in degradation rate is related to the size of its effective membrane area. The performance differences of different membrane types may be related to the effective surface area, catalyst loading, and mass transfer conditions within the reactor. Tubular multi-channel piezoelectric catalytic membranes have the best degradation effect, followed by single-tube membranes, and disc membranes have the lowest effect. Those skilled in the art can select the appropriate membrane type according to the actual engineering treatment capacity requirements.

[0079] The above results demonstrate that the silicon carbide piezoelectric catalytic membranes prepared in this application can effectively activate PMS to degrade organic pollutants, and the synergistic effect of PE-PMS results in a degradation rate of Rhodamine B that far exceeds that of its individual system.

[0080] Application Example 2: The piezoelectric catalytic membrane prepared in Example 1 was used to conduct a cyclic degradation experiment of Rhodamine B.

[0081] See Figure 5 Although the membrane degradation performance gradually decreased with the number of reactions, the degradation rate of Rhodamine B remained above 90% after 5 cycles, indicating that the piezoelectric catalytic membrane is reusable.

[0082] The piezoelectric catalytic membranes prepared in Example 1 and Comparative Example 1 were used to conduct a 5-cycle degradation experiment of Rhodamine B. The ion leaching concentrations before and after the degradation were measured and are shown in Table 2.

[0083] Table 2 Ion leaching concentrations before and after recycling of the piezoelectric catalytic membrane Referring to Table 2, the results show that the leaching concentrations of Ti and Ba ions in the catalytic membrane prepared by the silica-free sol in Comparative Example 1 were higher than those in the catalytic membrane prepared by the silica-containing sol in Example 1 before and after the cyclic reaction. The Ti / Ba leaching concentrations in Comparative Example 1 were approximately 11.96 times and 22.86 times higher than those in Example 1, respectively. This indicates that after the barium titanate piezoelectric catalytic membrane grown by the silica-free sol was subjected to ultrasonic activation, some barium titanate or TiO2 particles were shed and lost. After introducing the silica component, the Ti and Ba concentrations detected in the cyclic reaction solution were lower, indicating that the composite inducing layer helps to improve the leaching resistance of the catalytic membrane.

[0084] Finally, it should be noted that: The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A silicon carbide piezoelectric catalytic membrane, characterized in that, It includes a pure silicon carbide film substrate, a composite induction layer supported on the pure silicon carbide film substrate, and BaTiO3 particles supported on the composite induction layer; The composite induction layer comprises TiO2 and silicon-oxygen components; The BaTiO3 is barium titanate particles generated in situ on the surface of TiO2.

2. The silicon carbide piezoelectric catalytic membrane according to claim 1, characterized in that, The TiO2 component is anatase TiO2.

3. The silicon carbide piezoelectric catalytic membrane according to claim 1, characterized in that, The pure silicon carbide membrane is one of a single-channel tubular membrane, a multi-channel tubular membrane, or a sheet membrane.

4. A method for preparing a silicon carbide piezoelectric catalytic membrane, characterized in that, A pure silicon carbide film substrate is immersed in Ti-Si composite sol for impregnation and coating. After drying, it is calcined in an air atmosphere at 450-550℃. After calcination, it is immersed in a strong alkaline reaction solution containing barium source for hydrothermal reaction.

5. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 4, characterized in that, The Ti-Si composite sol is prepared as follows: tetrabutyl titanate is mixed with anhydrous ethanol, and acetylacetone is added to obtain solution A; deionized water, dispersant and anhydrous ethanol are mixed, tetraethyl orthosilicate is added, and the pH is adjusted to 2.0-2.5 with acid to obtain solution B; solution B is added dropwise to solution A, stirred and aged to obtain the Ti-Si composite sol.

6. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 5, characterized in that, The dispersing agent is polyvinylpyrrolidone; the mass of the polyvinylpyrrolidone is 3% to 10% of the mass of the tetrabutyl titanate; the molar ratio of the deionized water to the tetrabutyl titanate is (1.0 to 3.5):

1.

7. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 5, characterized in that, The mass of the silicon source in solution B, calculated as SiO2, accounts for 1% to 5% of the sum of the mass of the titanium source in solution A, calculated as TiO2, and the mass of the silicon source in solution B, calculated as SiO2.

8. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 4, characterized in that, The impregnation coating is performed by multiple impregnation and lifting processes, with 1 to 5 impregnations, each impregnation lasting 10 to 60 seconds and a lifting rate of 2 to 8 mm / s. After each impregnation, the coating is dried at 80 to 120°C for 5 to 15 minutes.

9. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 4, characterized in that, The strongly alkaline reaction solution provides an alkaline environment with KOH or NaOH and a barium source with Ba(OH)2.

10. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 9, characterized in that, The concentration of KOH or NaOH is 0.5–1.0 M.

11. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 9, characterized in that, The concentration of Ba(OH)2 is 0.03–0.1 M.

12. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 4, characterized in that, After the hydrothermal reaction is completed, the prepared silicon carbide piezoelectric catalytic membrane is taken out, rinsed with deionized water until neutral, and then dried.

13. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 4, characterized in that, The heating rate of the calcination is 1-3℃ / min, and the holding time of the calcination is 60-180min.

14. The method for preparing the silicon carbide piezoelectric catalytic membrane according to claim 4, characterized in that, The hydrothermal reaction temperature is 180–220°C, and the holding time is 18–48 hours.

15. The application of a silicon carbide piezoelectric catalytic membrane in the treatment of organic wastewater, wherein the silicon carbide piezoelectric catalytic membrane is the silicon carbide piezoelectric catalytic membrane according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation method of silicon carbide catalytic membrane with multi-layer structure

    CN114515587A

  • Piezoelectric photocatalytic self-cleaning hollow fiber ceramic membrane as well as preparation method and application thereof

    CN119926195A